Automated identification of multiple seizure-related and interictal epileptiform event types in the EEG of mice - Bergstrom, Rachel A.; Choi, Jee Hyun; Manduca, Armando; Shin, Hee-Sup; Worrell, Greg A.; Howe, Charles L. (NATURE PUBLISHING GROUP, 2013)
Visual scoring of murine EEG signals is time-consuming and subject to low inter-observer reproducibility. The Racine scale for behavioral seizure severity does not provide information about interictal or sub-clinical epileptiform activity. An automated algorithm for murine EEG analysis was developed using total signal variation and wavelet decomposition to identify spike, seizure, and other abnormal signal types in single-channel EEG collected from kainic acid-treated mice. The algorithm was validated on multi-channel EEG collected from gamma-butyrolacetone-treated mice experiencing absence seizures. The algorithm identified epileptiform activity with high fidelity compared to visual scoring, correctly classifying spikes and seizures with 99% accuracy and 91% precision. The algorithm correctly identifed a spike-wave discharge focus in an absence-type seizure recorded by 36 cortical electrodes. The algorithm provides a reliable and automated method for quantification of multiple classes of epileptiform activity within the murine EEG and is tunable to a variety of event types and seizure categories.
Keywords: TEMPORAL-LOBE EPILEPSY; NEURAL-NETWORK; SPIKE ACTIVITY; LINE LENGTH; KAINIC ACID; ONSET; ELECTROENCEPHALOGRAM; PREDICTION; DYNAMICS; KAINATE